The Bambuí Health and Aging Study (BHAS): factors associated with hospitalization of the elderly Projeto Bambuí: fatores associados a internações hospitalares entre idosos na comunidade - Henrique L. Guerra; Josélia O. A. Firmo; Elizabeth Uchoa; Maria Fernanda F. Lima-Costa (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2001)
This study aimed to identify factors associated with hospital admissions of the elderly. All residents of Bambuí, Minas Gerais State > or = 60 years (n = 1,742) were selected. Some 1,606 of these (92.2%) participated in the study. The dependent variable was the number of hospital admissions (none, one, and two or more) during the previous 12 months. Independent variables were grouped as enabling, predisposing, and need-related factors. The strongest associations with multiple hospital admissions were: living alone; financial constraints to purchase of medication; and various indicators of need (worse self-perceived health, more visits to physician, greater use of prescription medications, and history of coronary heart disease). Such variables could help identify older adults at greatest risk and thus prevent hospitalization. O estudo procura identificar fatores associados com internação hospitalar entre idosos. Foram selecionados todos os adultos residentes em Bambuí, Minas Gerais, com 60 ou mais anos (n = 1.742). Deste total, 1.606 (92,2%) participaram no estudo. A variável dependente era o número de internações hospitalares (0, 1 ou > ou = 2) nos últimos 12 meses. As variáveis independentes foram classificadas como facilitadoras, predisponentes e relacionadas a necessidades. As variáveis independentes que demonstraram associações mais fortes com o número de internações hospitalares foram: o fato de viver sozinho(a); restrições financeiras à aquisição da medicação prescrita e diversos indicadores de necessidade (percepção negativa da própria saúde, número maior de consultas médicas, maior uso de medicação com receita médica e história de doença coronariana). Estas variáveis poderiam ajudar a identificar os idosos com risco elevado de hospitalização e contribuir para medidas preventivas.